The Evolutionary Kaleidoscope of Rhodopsins - Bulzu, Paul-Adrian; Kavagutti, Vinicius S; Andrei, Adrian-Stefan; Ghai, Rohit (mSystems, 2022)
Rhodopsins are widely distributed across all domains of life where they perform a plethora of functions through the conversion of electromagnetic radiation into physicochemical signals. As a result of an extensive survey of available genomic and metagenomic sequencing data, we reported the existence of novel clades and exotic sequence motifs scattered throughout the evolutionary radiations of both Type-1 and Type-3 rhodopsins that will likely enlarge the optogenetics toolbox. We expanded the typical rhodopsin blueprint by showing that a highly conserved and functionally important arginine residue (i.e., Arg82) was substituted multiple times during evolution by an extensive amino acid spectrum. We proposed the umbrella term Alt-rhodopsins (AltRs) for all such proteins that departed Arg82 orthodoxy. Some AltRs formed novel clades in the rhodopsin phylogeny and were found in giant viruses. Some newly uncovered AltRs were phylogenetically close to heliorhodopsins, which allowed a closer examination of the phylogenetic border between Type-1 rhodopsins and heliorhodopsins. Comprehensive phylogenetic trees and ancestral sequence reconstructions allowed us to advance the hypothesis that proto-heliorhodopsins were a eukaryotic innovation before their subsequent diversification into the extant Type-3 rhodopsins. IMPORTANCE The rhodopsin scaffold is remarkably versatile and widespread, coupling light availability to energy production and other light-dependent cellular responses with minor alterations to critical residues. We described an unprecedented spectrum of substitutions at one of the most conserved amino acids in the rhodopsin fold, Arg82. We denoted such phylogenetically diverse rhodopsins with the umbrella name Alt-rhodopsins (AltR) and described a distinct branch of AltRs in giant viruses. Intriguingly, some AltRs were the closest phylogenetic neighbors to Heliorhodopsins (HeRs) whose origins have remained enigmatic. Our analyses of HeR origins in the light of AltRs led us to posit a most unusual evolutionary trajectory that suggested a eukaryotic origin for HeRs before their diversification in prokaryotes.
Keywords: rhodopsiny mikrobiální; optogenetics; Rhodopsin; fylogeneze; AltRs; rodopsin; Alt-rhodopsins; heliorhodopsins; rhodopsins; metagenomics; Rhodopsins, Microbial; Phylogeny